Jumping Ship Crew In Cruise Ship Crew Recruitment At PT. CWT - Nabila Nurul Ikhlas; Mustain, Iing; Abdurohman; Darsono, Nono (Nama Jurnal Akmi, 2024)
The purpose of the study was to determine the flow of the cruise ship crew recruitment process at PT. CWT, to find out what obstacles are experienced when recruiting cruise ship crew, and to find out a crew to meet the targets of the Norwegian Cruise Line. The study used a qualitative descriptive approach to case studies in the selected objects. Data collection in the study used data triangulation, namely observation, interviews, and documentation. The object of the study is PT. CWT Bandung. The results of the study were obtained. There are several factors that make crew take a long time to join or even cancel joining due to several factors that still often occur. The factors found in the recruitment process for ship crew at PT. CWT are often incomplete document requirements from the crew who apply or there are still many crew who are not proficient in English because they are required to take a marlin test whose results must be 70% and the interview must also be in English. Efforts were made to meet the target of Norwegian Cruise Line to always fill every position that was needed, seeking relations such as shipping schools to be informed that there were vacancies for certain positions that were needed.